2014
DOI: 10.1039/c4em00225c
|View full text |Cite
|
Sign up to set email alerts
|

Coastal microbial quality of surface sediments in different environments along the Italian coast

Abstract: In order to improve sediment handling following dredging operations, this study aims to statistically derive ranges of distribution for certain microbiological parameters, according to four environmental types inspired by Italian legislation on seaports: ports of international/national importance, ports of regional importance, port channels in brackish environments, and marine coastal areas. A national database was developed using microbiological data from technical reports available at the Italian Ministry of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…This is consistent with the findings of Skanavis and Yanko [ 37 ] that the spore-forming obligate anaerobe C. perfringens is more persistent in sediment than E. coli or enterococci. As in the present study, Chiaretti et al [ 18 ] observed the highest load of C. perfringens in the sediment of large ports, which are characterized by favorable conditions for longer survival of these bacteria, such as fine-grained sediment with higher organic matter content [ 5 ]. Because of its properties, C. perfringens is considered a persistent indicator of a long-term fecal contamination [ 4 ] and the presence of protozoan cysts end enteric viruses [ 52 ].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This is consistent with the findings of Skanavis and Yanko [ 37 ] that the spore-forming obligate anaerobe C. perfringens is more persistent in sediment than E. coli or enterococci. As in the present study, Chiaretti et al [ 18 ] observed the highest load of C. perfringens in the sediment of large ports, which are characterized by favorable conditions for longer survival of these bacteria, such as fine-grained sediment with higher organic matter content [ 5 ]. Because of its properties, C. perfringens is considered a persistent indicator of a long-term fecal contamination [ 4 ] and the presence of protozoan cysts end enteric viruses [ 52 ].…”
Section: Discussionsupporting
confidence: 59%
“…The Convention also specifies the maximum allowed amounts of discharged viable organisms and indicator microbes during BW discharge, E. coli , intestinal enterococci and Vibrio cholerae ( V. cholerae ), as part of the D-2 standard. The studies on microbial contamination of seaports and their potential to pollute adjacent coastal areas are rather limited [ 11 , 18 , 19 , 20 , 21 , 22 , 23 ], and there is a need for further research.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study investigating the patterns and spatial-temporal dynamics of seawater and sediment faecal contamination in a large number of commercial ports and adjacent urbanized areas situated in the same basin. Despite increasing awareness of faecal pollution in ports (Chiaretti et al, 2014), investigations of FIB levels in seawater or sediments are few and sparse (Jeng and Han, 1994;Wong et al, 1995;Luna et al, 2012;Ng et al, 2015;Dheenan et al, 2016), and no systematic studies have investigated the spatial-temporal dynamics of FIB contamination in ports. According to the present findings, FIB pollution was high in all ports, often much higher than in the adjacent coastal Table 2 Summary of statistical analyses (two-way ANOVA) carried out to test for spatial (Port) and seasonal (Season) differences in FIB abundance in seawater and sediment samples from the 12 ports.…”
Section: Discussionmentioning
confidence: 99%
“…Their concentrations in seawater have been reported to be higher near harbours than in coastal areas immediately outside them (Dheenan et al, 2016), while high levels of coprostanol, an indicator of sewage pollution, have been measured in sediments collected from a large industrial port (Jeng and Han, 1994). A recent study of Italian ports -small ports, large ports hosting international traffic as well as coastal areashas found that faecal pollution was highest in the larger ports (Chiaretti et al, 2014).…”
Section: Introductionmentioning
confidence: 99%